Principles for determining the Air Force active/reserve mix - Robbert, Albert A., 1944- (RAND, 1999)
Although the mix of active and reserve forces constituting the total Air Force has shifted during the last decade's force drawdown, reductions have not been proportional and may not have taken into consideration effects on other components. This report sets forth a set of principles to help force planners and programmers recognize the implications for the cost, effectiveness, sustainability, and popular and political support of military forces. A framework is provided for integrating the range of considerations that decisionmakers face and for gaining perspective on the arguments voiced by interest groups who hope to influence the force mix. The authors find that cost considerations can cut in opposite directions depending on whether the force is being optimized for major theater war preparedness or for peacetime contingency operations.